A study of pulsating heat pipes for electronic cooling - Tong, Boon Yong. (2008)
This project is focused on the study of pulsing heat pipes (PHP) as cooling devices for thermal management in electronic systems. The configurations of the PHP studied are the open-loop and closed-loop designs. The work carried out includes flow visualization, experimental investigations and theoretical modeling.